Plant adaptation : molecular genetics and ecology - Cronk, Quentin C. B. (NRC Press, 2004)
The Proceedings of an International Workshop sponsored by the UBC Botanical Garden and Centre for Plant Research held December 11-13, 2002 in Vancouver, British Columbia, Canada.